Simulation of micro-scale shear bands using peridynamics with an adaptive dynamic relaxation method. (January 2018) - Luo, J.; Ramazani, A.; Sundararaghavan, V.
Abstract: A peridynamic (PD) implementation of crystal plasticity with an adaptive dynamic relaxation method is presented. Non-ordinary state-based peridynamics and the Newmark's dynamic method with artificial damping are employed to capture strain localizations in polycrystalline microstructures based on a rate-independent crystal plasticity model. Numerical simulations for planar polycrystals are conducted under plane strain pure shear and compression, respectively. The computational efficiency of the explicit PD model is demonstrated to be superior to an implicit PD model for modeling crystal plasticity. The stress field distribution, texture formation, and homogenized stress-strain response predicted by the finite element method and the new dynamic PD model are compared. Finer localization bands are observed in the latter model. The origin and evolution of these shear bands are studied by PD simulations during deformation of three polycrystals with different orientation distributions. Emphasis is placed on the accuracy and efficiency of the adaptive dynamic relaxation method working with crystal plasticity PD models.